Long-term development of palsas and other permafrost-cored mounds in mountainous terrain, Wolf Creek, southern Yukon. - Coultish, Tara L. (University of Ottawa (Canada), 2002)
Fifty-one frost mounds were examined in Wolf Creek, Yukon Territory (60°30'N, 135°13'W) at an elevation of 1235 m a.s.l. Cryostratigraphic analyses and aerial photographic interpretation were undertaken to investigate the origin and longevity of the mounds, and to assess their utility as climatic indicators. It was determined that 37 mounds were palsas, as evidenced by their dimensions, cryostructure of segregated ice and location within a fen; one mound was a frost blister, as evidenced by its core of intrusive ice; one mound may have been a compound form, with segregation and possibly intrusive ice; and 12 mounds were termed aggradational permafrost mounds as their cores were of segregated ice but they did not fit the locational requirements to be palsas. Aerial photographs, spanning the period from 1946 to 2001, showed that palsas at the study site have been aggrading and degrading continually over the past 55 years, and are continuing to do so. (Abstract shortened by UMI.)
Keywords: Physical Geography.